Environmental hazards of lithium batteries - Kuzmin, K. S. (ТДАТУ, 2021)
If batteries are disposed correctly by transferring them to disposal facilities, a significant reducing of harmful substances ingress into the soil will be achieved. Developing two directions is reasonable: modernization of recycling technologies as well as production technology. Thanks to the cutting-edge technologies zero emission of harmful components can be achieved. If manufacturers focuse on invention of more effective technologies that will have the effect of preserving, the risks of harm to the environment are going to be reduced. The invention of a new type of battery can revolutionize not only the automotive industry but also the field of mobile electronics.
Keywords: lithium-ion batteries; hazards of lithium batteries